2014
DOI: 10.1051/kmae/2014018
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity defends against the invasion of Nile tilapia (Oreochromis niloticus)

Abstract: Key-words:Nile tilapia (Oreochromis niloticus), biodiversity resistance, biological invasion, species richness, biomass Nile tilapia (Oreochromis niloticus) is one of the most widely cultured species globally and has successfully colonized much of the world. Despite numerous studies of this exotic species, how differences in native communities mitigate the consequences of Nile tilapia invasion is unknown. Theory predicts that communities that are more diverse should be more resistant to exotic species, an effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…In China, Nile tilapia was initially introduced into Guangdong Province for aquaculture in 1957, and it has since become an important aquaculture species in the southern part of the country (Gu et al, ). However, recent evidence suggests that it has escaped aquaculture facilities and is now naturalised in the wild, and its distribution has expanded to most of the river systems in south China (Blackburn et al, ; Shuai, Li, Chen, Li, & Lek, ).…”
Section: Introductionmentioning
confidence: 99%
“…In China, Nile tilapia was initially introduced into Guangdong Province for aquaculture in 1957, and it has since become an important aquaculture species in the southern part of the country (Gu et al, ). However, recent evidence suggests that it has escaped aquaculture facilities and is now naturalised in the wild, and its distribution has expanded to most of the river systems in south China (Blackburn et al, ; Shuai, Li, Chen, Li, & Lek, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the relative contribution of resident diversity to invasion resistance varies across different exotic taxa and spatial scales (Davies et al, 2010;Gu et al, 2014). Of course, this theory does not hold up well for fish invasions into streams and estuaries (Gu et al, 2014;Meador et al, 2003;Moyle & Light, 1996). This theory has been well explained in many aquatic ecosystems.…”
Section: Predictive Indicators 3: Loss Of Biodiversity Accelerates mentioning
confidence: 99%
“…The historical data were collected when the invasive fish species had not established, and these results showed that biotic resistance was greater in the invasion process of non-native fish species. The decrease of native species caused by environmental changes, overfishing and other factors may generate large numbers of empty niches, which will accelerate the speed of invasion (Carey & Wahl, 2010;Gu et al, 2014). Sampling date and county-level administrative regions where sites were located according to the People's Government of Guangdong Province.…”
Section: Predictive Indicators 3: Loss Of Biodiversity Accelerates mentioning
confidence: 99%
See 2 more Smart Citations